Sustainable evaluation procedure for residual commingled waste after recycling, factoring in the percentage content of solid components - Zbigniew Jelonek; Iwona Jelonek; Przemysław Rompalski; Justyna Guzy-Proc (PLoS ONE, 2026)
The management of residual municipal waste after recycling is becoming an increasingly problematic procedure, while the challenges related to this process are multi-dimensional and encompass environmental, economic and social factors. As per the recommendations of the European Union, it is more beneficial for the residual fraction to undergo disposal via waste-to-energy conversion in specialist incineration plants and monitored low-power boilers than by landfilling. Such a process not only limits the negative impact on the environment that is characteristic of landfilling but also makes it possible to obtain additional electric and thermal energy. In this paper, the authors indicate the key role of the precise determination of solid waste composition before thermal conversion or storage. They also present a new optical method of residual fraction analysis for solid component proportion determination. It should be stressed that the precise knowledge of the waste composition can streamline decision making as regards selective waste recycling and reprocessing, including, e.g., excess organic matter separation. The conducted analyses showed that with an increase in the organic fraction content in waste from 30% to 90%, there is an increase in the emission of, among other things, particulate matter from 124.96 mg/m 3 to 393.47 mg/m 3 , CO from 819.06 mg/m 3 to 2161.67 mg/m 3 , and VOCs from 0 mg/m 3 to 117.1 mg/m 3 .